Risk factors for fungal co-infections in critically ill COVID-19 patients, with a focus on immunosuppressants - Ezeokoli, Obinna T.; Gcilitshana, Onele; Pohl, Carolina H. (MDPI, 2021)
Severe cases of coronavirus disease 2019 (COVID-19) managed in the intensive care unit are prone to complications, including secondary infections with opportunistic fungal pathogens. Systemic fungal co-infections in hospitalized COVID-19 patients may exacerbate COVID-19 disease severity, hamper treatment effectiveness and increase mortality. Here, we reiterate the role of fungal co-infections in exacerbating COVID-19 disease severity as well as highlight emerging trends related to fungal disease burden in COVID-19 patients. Furthermore, we provide perspectives on the risk factors for fungal co-infections in hospitalized COVID-19 patients and highlight the potential role of prolonged immunomodulatory treatments in driving fungal co-infections, including COVID-19-associated pulmonary aspergillosis (CAPA), COVID-19-associated candidiasis (CAC) and mucormycosis. We reiterate the need for early diagnosis of suspected COVID-19-associated systemic mycoses in the hospital setting.
Keywords: COVID-19; Fungal co-infections; Corticosteroid treatment; COVID-19-associated candidiasis; COVID-19-associated pulmonary aspergillosis; Mucormycosis